EFFECT OF ETHANOLIC EXTRACT OF THYME AND OLIVE LEAVE IN QUALITY CHARACTERISTIC OF LAMB PATTIES DURING STORAGE - Anwar, Hozan. M.; Baker, I. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of this experiment was to evaluate the effect of adding different levels of each of olive leaf extract (OLE) and thyme leaf extract (TLE) and their combination in some physicochemical, microbial, and sensory characteristic of lamb patties stored either at 4c° for 12 days or at -18c° for 120 days. Results revealed that there are a steady rise (p